Processo como direito fundamental: a desconstrução do “processo justo” e a edificação do devido processo legal - Silva Filho, Antônio José Carvalho da (2021)
The thesis is divided into three parts. The first investigates the distortion of the (procedural) due process concept, with its mixture with the exercise of jurisdictional power, which culminated in the formation of the “fair process” (giusto processo, proceso justo, processo justo) theory. This development took place within “procedural instrumentalism” theory and its related movements, “evaluative formalism” and “neoprocessualism”, with great influence from the neoconstitutionalist doctrine. The second part establishes the dogmatic bases for the analysis of basic rights, with a special tendency towards the liberal theory of basic rights, namely the German. At this point, the aim is to establish the basic concepts and structure the method of confronting interventions within the scope of protection of basic rights. Finally, in the third part, the dogmatics of the basic rights of due process are developed, with the establishment of their respective areas of protection and the confrontation of the respective interventions